Graphical User Interface for Capacity Planning in Long Term Evolution (International Journal of Engineering and Computer Science, 2014)
Getting the most out of the network, meeting subscriber demands and developing new revenue growth plans, is business critical and one of the key drivers in the uptake of LTE as a new technology, so radio network planning is an essential process for operators who are looking to make the most of their networks. In order to achieve the radio network planning, there are a number of stages that are typically performed, these includes: Initial planning, detailed planning and optimization. The initial phase of network planning is known as dimensioning .The purpose of dimensioning is to estimate the required number of radio base stations needed to support a specified traffic load in an area. Dimensioning has two phases: coverage planning phase and capacity planning phase. This paper focuses on the capacity planning phase. A GUI tool was designed and simulated using MATLAB program to perform it. The tool provides the number of sites required in the capacity planning phase.